Contributions of Reward Sensitivity to Ventral Striatum Activity Across Adolescence and Early Adulthood. Issue 3 (13th March 2018) - Schreuders, Elisabeth; Braams, Barbara R.; Blankenstein, Neeltje E.; Peper, Jiska S.; Güroğlu, Berna; Crone, Eveline A.
Abstract : It was examined how ventral striatum responses to rewards develop across adolescence and early adulthood and how individual differences in state‐ and trait‐level reward sensitivity are related to these changes. Participants (aged 8–29 years) were tested across three waves separated by 2 years (693 functional MRI scans) in an accelerated longitudinal design. The results confirmed an adolescent peak in reward‐related ventral striatum, specifically nucleus accumbens, activity. In early to mid‐adolescence, increases in reward activation were related to trait‐level reward drive. In mid‐adolescence to early adulthood decreases in reward activation were related to decreases in state‐level hedonic reward pleasure. This study demonstrates that state‐ and trait‐level reward sensitivity account for reward‐related ventral striatum activity in different phases of adolescence and early adulthood. Abstract : The title for this Special Section isThe Developing Brain: Evidence for Plasticity during Childhood and Adolescence, edited by Amanda E. Guyer, Koraly Pérez‐Edgar, and Eveline A. Crone